Analisis Faktor yang Mempengaruhi Pengembangan UMKM Ikan Pindang di Kecamatan Herlang Kabupaten Bulukumba Sulawesi Selatan - Ichwan, Aulia Magfhira; Riskiyani, Riskiyani; Zailan, Ahmad; Astaman, Putra (Agriculture and Socio-Economic Journal, 2025)
Pindang fish processing micro, small and medium enterprises (MSMEs) in Bulukumba district, which are mostly managed by women, play an important role in the local economy, but also face various constraints that hinder their growth. This study aims to identify internal and external factors that influence the development of pindang fish processing MSMEs. A descriptive qualitative approach was used in this study, with data collection methods in the form of in-depth interviews, observation, and documentation. The results show that the dominant internal factors are limited managerial skills and low product quality, which are influenced by non-standardized production processes and lack of attention to sanitation. Externally, although there is high market demand, the main challenges lie in marketing, distribution, and lack of business legality. The government provides support in the form of training and equipment assistance, but the mismatch between assistance and the real needs of MSME actors is still an obstacle. This study suggests that the government and related parties pay more attention to improving the quality of human resources, better production systems, and the utilization of technology to improve product quality and expand markets. From these results, it can be concluded that to encourage the sustainability and growth of pindang fish MSMEs, it is necessary to improve the quality of human resources, improvements in production systems, and the use of technology to improve product quality and expand markets. This will help MSME actors to overcome existing challenges and capitalize on available market potential.